Study of Spectral, Thermal and Electrochemical Properties of New Thermally Stable Blue Light Emitting Materials Based Aromatic Polyamides - Rashid, Azhar Kamil (Asian Journal of Chemistry, 2016)
In this study, new triphenylamine with aromatic diacid monomers, 4,4'-dicarboxy-4''-acetyl-triphenylamine (AC1), 4,4'-dicarboxy-4''-ethyl-triphenylamine (AC2), 4,4'-dicarboxy-4''-methoxy-triphenylamine (AC3) were successfully synthesized by the aromatic nucleophilic displacement reaction of 4-fluorobenzonitrile with three aniline-derivatives using sodium hydride as the base, followed by alkaline hydrolysis of the di-cyanides intermediates (CY1, CY2, CY3). From these di-acids monomers, a series of poly(amine-amide)s were prepared by the phosphorylation poly-condensation reaction with different aromatic diamines. FTIR, 1H and 13C NMR spectroscopic techniques were used to identify the chemical structures of all resultant compounds and poly(amine-amide)s. These aromatic poly(amine-amide)s have a good solubility in several organic solvents and gave strong and tough thin films via solution casting. They exhibited excellent thermal stability associated with high glass transition temperatures (Tg). In dilute N-methyl pyrrolidone solution, these polymers exhibited a strong photoluminescence in the blue region. Cyclic voltammetry of the results polyamides films cast onto an ITO-coated glass substrate in dry acetonitrile containing 0.1 M of tetrabutylammonium perchlorate as an electrolyte exhibited one oxidation redox couples.